Original paperOral premalignant lesions: epidemiological and clinical analysis in the northern Polish population - Starzyńska, Anna; Pawłowska, Anita; Renkielska, Dorota; Michajłowski, Igor; Sobjanek, Michał; Błażewicz, Izabela (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction: Leukoplakia is the most common potentially malignant condition of the oral cavity. Aim : Epidemiological and clinical analysis of patients with oral leukoplakia (OL) diagnosed and treated in the Department of Maxillofacial and Oral Surgery, Medical University of Gdansk. Material and methods : The study was retrospective and prospective. Among 55 911 patients diagnosed and treated in the Department in 1999–2009, 204 people with OL were selected. The material includes 104 women and 100 men with an average age of 58.1. Most of the patients were in the age group of 50–70 years, average age was 58.1. Results : The most common concomitant disease was diabetes. More than 88% of the patients declared occurrence of OL predisposing development factors (50.49% – cigarette smoking). Three hundred and twenty foci of OL were found among patients. Homogeneous OL dominated (72.05%). Multifocal OL was diagnosed in 58.3% of patients. The most common location of lesions was buccal mucosa (52.2%). Cancers developed on the basis of OL in 7 patients (3.43%). The percentage of malignant transformation was 12.19% for untreated patients and 1.41% for treated patients. The floor of the oral cavity was proven to be the location of the highest risk of oral squamous cell carcinoma. Patients with diabetes may be more likely to develop OL. The risk of malignant transformation is relatively high. In our material it was equal to 3.43%. Conclusions : Cigarette smoking is the most important factor, which can influence the effectiveness of treatment.